Determining content strategy: the case of one championship Indonesia’s youtube channel - Muhammad Rizatha; Raden Aswin Rahadi (Universitas Majalengka, 2022)
Today the internet makes the world connected. Therefore, marketing techniques have begun to shift from conventional to digital methods. In this digital world, content is considered key, not only as part of the promotion method but also as a communication bridge between brands and consumers to create credibility and loyalty. However, with so many choices of social media platforms with different characteristics and trends, content creators need to know the expectations and tastes of their consumers. In this study, the authors use a case study of a sports property media company, ONE Championship, which launched a social media platform specifically for the Indonesian market. Since October 2020, the company headquartered in Singapore has launched a YouTube channel dedicated to the Indonesian market. Through this research, the author hopes to determine the right content strategy for the ONE Championship Indonesia YouTube channel according to local consumers' tastes. This study uses qualitative methods and thematic analysis. Primary data was obtained through interviews with three ONE Championship employees operating the Indonesian-language ONE Championship YouTube platform and seven ONE Championship consumers in Indonesia. The findings of this study produce a variety of data on consumer tastes in content, consumer habits in consuming content, and consumer expectations for future content. The author then re-analyzed the data to find a content strategy that the ONE Championship team can implement on its Indonesian YouTube channel over the next two years.